Voir et être vu du sommet : le cas de Needles Lookout dans « Sitting on Top of the World » de T.C. Boyle - Caroline Roussel (Anglophonia)
Written in 1989, T.C. Boyle’s short story "Sitting on Top of the World"1 is a rewriting of the topos of the solitary mountain, which usually brings to mind a hermit-like style of life dedicated to the exploration of existential crises, and thus implying an ensuing spiritual quest, amidst the hardships of the wilderness. Boyle’s story takes a new stance on the lone mountain since it becomes the place where the vulnerability of mankind is staged rather than the serenity and the superiority of Man over Nature. Visual perception, which lies at the heart of the story, is not merely a euphoric experience where the eye roams over landscape and printed page, but gradually becomes a destabilizing and traumatic phenomenon, thereby revealing the quintessential insecurity of human life, an insecurity most of Boyle’s characters are prone to.